2014
DOI: 10.1103/physreve.90.023013
|View full text |Cite
|
Sign up to set email alerts
|

Statistical scaling of pore-scale Lagrangian velocities in natural porous media

Abstract: We investigate the scaling behavior of sample statistics of pore-scale Lagrangian velocities in two different rock samples, Bentheimer sandstone and Estaillades limestone. The samples are imaged using x-ray computer tomography with micron-scale resolution. The scaling analysis relies on the study of the way qth-order sample structure functions (statistical moments of order q of absolute increments) of Lagrangian velocities depend on separation distances, or lags, traveled along the mean flow direction. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Dashtian et al (2011) concluded that these formations are layered based on complete suites of well logs at each of the three sites. We note further that a similar dual-scaling phenomenon has recently been reported by Siena et al (2014) vis-á-vis porosities and specific surface areas imaged using X-ray computer microtomography throughout a millimeter-scale block of Estaillades limestone, at a spatial resolution of 3.3 µm, as well as Lagrangian velocities computed by solving the Stokes equation in the sample pore space.…”
Section: Statistical Scaling Of Neutron Porosity Incrementssupporting
confidence: 83%
See 2 more Smart Citations
“…Dashtian et al (2011) concluded that these formations are layered based on complete suites of well logs at each of the three sites. We note further that a similar dual-scaling phenomenon has recently been reported by Siena et al (2014) vis-á-vis porosities and specific surface areas imaged using X-ray computer microtomography throughout a millimeter-scale block of Estaillades limestone, at a spatial resolution of 3.3 µm, as well as Lagrangian velocities computed by solving the Stokes equation in the sample pore space.…”
Section: Statistical Scaling Of Neutron Porosity Incrementssupporting
confidence: 83%
“…Statistical scaling of hydrogeological data such as permeability or hydraulic conductivity has been studied amongst others by Painter (2001), Meerschaert et al (2004), Kozubowski et al (2006), Siena et al (2012Siena et al ( , 2014, Riva et al (2013bRiva et al ( , 2013c, and Guadagnini et al (2012Guadagnini et al ( , 2013Guadagnini et al ( , 2014. Whereas research in the subsurface hydrology literature has not addressed specifically the distribution and statistical scaling of extreme incremental values, spatial correlations between values significantly in excess of the mean have been studied vis-à-vis variables such as transmissivity and their relevance to transport processes has been highlighted.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies are notably challenging in the case of carbonate systems, due to the complex topological setting of the pore space (e.g., Siena et al 2014 and references therein), which is often associated with low porosity values (Hebert et al 2014 and references therein). A solid body of experimental evidences illustrates that the porosity increase resulting from carbonate dissolution is usually correlated with the increase of permeability.…”
Section: Introductionmentioning
confidence: 99%
“…Practical difficulties associated with the way one can rigorously include pore-scale modeling in the analysis of typical laboratory and field-scale settings lead to depicting of solute transport in such media through effective models [14,27,38,39,45]. Several alternative modeling options are available in this context, a common choice being a continuum-based representation grounded on the standard advection-dispersion equation (ADE) on which we focus here.…”
Section: Introductionmentioning
confidence: 99%